2014
DOI: 10.1182/blood.v124.21.267.267
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibitors of LSD1 Promote Differentiation of Myeloid Leukemia Cells through a Mechanism Independent of Histone Demethylation

Abstract: Lysine Specific Demethylase 1 (LSD1 or KDM1A) is one of a number of epigenetic regulators which have recently emerged as candidate therapeutic targets in acute myeloid leukaemia (AML). It is a flavin adenine dinucleotide (FAD) dependent homolog of the amine oxidase family with an ability to demethylate monomethyl or dimethyl lysine 4 (K4) of histone H3, in addition to other substrates. Pharmacological inhibitors of LSD1 such as the tranylcypromine derivatives have already commenced evaluation in early phase cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…This is in line with the reported observation that reversible and irreversible KDM1A inhibitors provoke the disruption of the KDM1A:GFI1 interaction (Lynch et al, 2014) and eviction of the protein from part of its genomic target sites (McGrath et al, 2016). More specifically, Lynch et al (2014) reported that the differentiation block of THP1 AML cells does not depend on the H3K4me2 demethylase activity of KDM1A but that drug-induced physical separation of GFI1 from KDM1A causes THP1 AML cells to undergo differentiation. Fast inhibitor-mediated dissociation of KDM1A from the SNAG domain of GFI1 may explain the rapid transcriptional responses that precede the changes in the H3K4 methylation levels described in the previous section.…”
Section: Chemoproteomics-based Profiling Of Kdm1a Protein-protein Intsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with the reported observation that reversible and irreversible KDM1A inhibitors provoke the disruption of the KDM1A:GFI1 interaction (Lynch et al, 2014) and eviction of the protein from part of its genomic target sites (McGrath et al, 2016). More specifically, Lynch et al (2014) reported that the differentiation block of THP1 AML cells does not depend on the H3K4me2 demethylase activity of KDM1A but that drug-induced physical separation of GFI1 from KDM1A causes THP1 AML cells to undergo differentiation. Fast inhibitor-mediated dissociation of KDM1A from the SNAG domain of GFI1 may explain the rapid transcriptional responses that precede the changes in the H3K4 methylation levels described in the previous section.…”
Section: Chemoproteomics-based Profiling Of Kdm1a Protein-protein Intsupporting
confidence: 87%
“…CTBP1 does not itself contain a SNAG domain, but has been described to interact with proteins that do (Kuppuswamy et al, 2008). This is in line with the reported observation that reversible and irreversible KDM1A inhibitors provoke the disruption of the KDM1A:GFI1 interaction (Lynch et al, 2014) and eviction of the protein from part of its genomic target sites (McGrath et al, 2016). More specifically, Lynch et al (2014) reported that the differentiation block of THP1 AML cells does not depend on the H3K4me2 demethylase activity of KDM1A but that drug-induced physical separation of GFI1 from KDM1A causes THP1 AML cells to undergo differentiation.…”
Section: Chemoproteomics-based Profiling Of Kdm1a Protein-protein Intsupporting
confidence: 56%
“…Multiple oral LSD1 inhibitors have already been undergoing phase I or IIa clinical trial in patients with AML ( https://clinicaltrials.gov/ ; ORY-1001 in phase I/IIa study; GSK2879552 in phase I study). In addition, we noticed that Lynch's group reported that physical association of LSD1 with transcription factors such as GFI1 is essential to maintain the differentiation block in AML and tranylcypromine-derivative inhibitors target this novel scaffolding function of LSD1, rather than its histone demethylase activity, to promote differentiation of AML cells [ 76 ]. It suggests that LSD1 might regulate myeloid differentiation and oncogenic proliferation on at least three dimensions: the first one is histone modification, such as H3K4 methylation; the second is non-histone protein methylation, such as p53-K372 methylation; and the last one is non-enzymatic scaffolding function, such as LSD1-GFI1 interaction in MLL-AF9 translocated AML, indicating the complexity of LSD1 function in the different cell contexts.…”
Section: Discussionmentioning
confidence: 99%
“…105 In vitro studies have found that LSD1 inhibitors do not significantly increase lysine methylation, and inhibition of LSD1-mediated transcriptional repression may contribute to its therapeutic effect. 106 Finally, emerging evidence supports the ability of LSD1 inhibitors, including tranylcypromine, to induce all-trans retinoic acid susceptibility in nonacute promyelocytic leukemia AML. 107 Phase 1 studies of multiple LSD1 inhibitors (INCB059872, IMG-7289, tranylcypromine) in AML are currently underway as monotherapy and combination therapy with all-trans retinoic acid or HMAs (Table 3).…”
Section: Bromodomain Inhibitorsmentioning
confidence: 95%